Egy határkiigazítási elképzelés Trianon után (1920 szeptember) - Sarnyai, Csaba Máté (Közép-Európai Közlemények, 2011)
Defining the Hungarian borders after WWI was controlled primarily by the 4 June 1920 treaty of Trianon. To decide on the borders described in the peace treaties and drawn on maps was a long process. Hungary was given certain, though by no means wide maneuvering space due to the letter attached to the reply to Hungarian peace delegation president Albert Apponyi from the Allied Powers (the document is better known as the Mitterand-letter). It could play a role in the creation of a memorandum about border modification concerning the area of Szeged; this memorandum was written in September of 1920, thus before the creation of Committees of Border Definition in June of 1921. The aim of the present paper is to contextualize, examine and evaluate the importance of such an attached letter. Most certainly, numerous similar documents must have been composed, but, according to our research, they are nowhere to be found yet. Hopefully, this paper will also facilitate the intensification of the search for these.